Antitumor effects of tyropeptin‐boronic acid derivatives: New proteasome inhibitors. Issue 12 (21st October 2014) - Momose, Isao; Abe, Hikaru; Watanabe, Takumi; Ohba, Shun‐ichi; Yamazaki, Kanami; Dan, Shingo; Yamori, Takao; Masuda, Tohru; Nomoto, Akio
<x xml:space="preserve">Abstract</x> The proteasome degrades numerous regulatory proteins that are critical for tumor growth. Thus, proteasome inhibitors are promising antitumor agents. New proteasome inhibitors, such as tyropeptins and tyropeptin‐boronic acid derivatives, have a potent inhibitory activity. Here we report the antitumor effects of two new tyropeptin‐boronic acid derivatives, AS‐06 and AS‐29. AS‐06 and AS‐29 significantly suppress the degradation of the proteasome‐sensitive fluorescent proteins in HEK293PS cells, and induce the accumulation of ubiquitinated proteins in human multiple myeloma cells. We show that these derivatives also suppress the degradation of the NF‐κB inhibitor IκB‐α and the nuclear translocation of NF‐κB p65 in multiple myeloma cells, resulting in the inhibition of NF‐κB activation. Furthermore, we demonstrate that AS‐06 and AS‐29 induce apoptosis through the caspase‐8 and caspase‐9 cascades. In a xenograft mouse model, i.v. administration of tyropeptin‐boronic acid derivatives inhibits proteasome in tumors and clearly suppresses tumor growth in mice bearing human multiple myeloma. Our results indicate that tyropeptin‐boronic acid derivatives could be lead therapeutic agents against human multiple myeloma.